Do current income and annual income measures provide different pictures of Britain's income distribution? - René Böheim; Stephen P. Jenkins (Deutsches Institut für Wirtschaftsforschung (DIW), 2000)
Most UK surveys, including those used each year to derive the official UK income distribution statistics (?Households Below Average Income?), provide measures of current household income rather than annual household income, which is the measure used in most other countries. Using British Household Panel Survey data, we examine whether estimates of Britain's income distribution and its trends are sensitive to the choice between current and annual income measures. The main finding is that current and annual income measures provide remarkably similar results. We explore why.
Keywords: 330; Einkommensverteilung; Haushaltsbudget-Statistik; Haushaltseinkommen; Statistische Methode; Großbritannien